New Insights Into the Backbone Phylogeny and Character Evolution of Corydalis (Papaveraceae) Based on Plastome Data - Xu, Xiaodong; Li, Xuexiu; Wang, Dong (Frontiers in Plant Science, 2022)
A robust backbone phylogeny is fundamental for developing a stable classification and is instructive for further research. However, it was still not available for Corydalis DC., a species-rich (> 500 species), ecologically and medically important, but taxonomically notoriously difficult genus. Here, we constructed backbone phylogeny and estimated the divergence of Corydalis based on the plastome data from 39 Corydalis species (32 newly sequenced), which represent ca. 80% of sections and series across this genus. Our phylogenetic analyses recovered six fully supported main clades (I–VI) and provided full support for the majority of lineages within Corydalis. Section Archaeocapnos was unexpectedly turned out to be sister to the rest of the subg. Corydalis s. l. (clades IV–VI), thus treating as a distinct clade (clade III) to render all the main clades monophyletic. Additionally, some unusual plastome structural rearrangements were constantly detected within Corydalis and were proven to be lineage-specific in this study, which, in turn, provided further support to our phylogeny. A segment containing five genes (trnV-UAC–rbcL) in the plastome's LSC region was either normally located downstream of the ndhC gene in clade I species or translocated downstream of the atpH gene in clade II species or translocated to downstream of the trnK-UUU gene in clade III–VI species. The unique large inversion (ca. 50 kb) in the plastome LSC region of clade III species, representing an intermediate stage of the above translocation in clades IV–VI, firmly supported clade III as a distinct and early diverged clade within this large lineage (clades III–VI). Our phylogeny contradicted substantially with the morphology-based taxonomy, rejected the treatment of tuberous species as an independent evolutionary group, and proved that some commonly used diagnostic characters (e.g., root and rhizome) were results of convergent evolution, suggestive of unreliability in Corydalis. We dated the origin of crown Corydalis to the early Eocene (crown age 49.08 Ma) and revealed possible explosive radiation around 25 Ma, coinciding with the drastic uplift of the Qinghai-Tibetan Plateau in Oligocene and Miocene. This study provided the most reliable and robust backbone phylogeny of Corydalis to date and shed some new insights on the evolution of Corydalis.